Effect of Ammonium Ions on the Induction of Nitrite Reductase in Neurospora crassa - Chang, H. C. P. (1976)
Results with strain am-la, a glutamate dehydrogenaseless mutant, showed that ammonium ions must first be metabolized in order to repress nitrite reductase in Neurospora.